Bio-oil production from oil palm biomass via subcritical and supercritical hydrothermal liquefaction - Chan, Y.H. (Elsevier, 2014)
This paper presents the studies on the liquefaction of three types of oil palm biomass; empty fruit bunch (EFB), palm mesocarp fiber (PMF) and palm kernel shell (PKS) using water at subcritical and supercritical conditions. The effect of temperature (330, 360, 390 °C) and pressure (25, 30, 35 MPa) on bio-oil yields were investigated in the liquefaction process using a Inconel batch reactor. The optimum liquefaction condition of the three types of biomass was found to be at supercritical condition of water i.e. at 390 °C and 25 MPa, with PKS yielding the maximum bio-oil yield of 38.53 wt, followed by EFB and PMF, with optimum yields of 37.39 wt and 34.32 wt, respectively. The chemical compositions of the bio-oils produced at optimum condition were analyzed using GC-MS and phenolic compounds constituted the major portion of the bio-oils, with other minor compounds present such as alcohols, ketones, aromatic hydrocarbons and esters. © 2014 Elsevier B.V. All rights reserved.